2018
DOI: 10.1002/jso.25314
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of sentinel lymph node biopsy for thin melanoma is associated with distance traveled for care

Abstract: Background Sentinel lymph node biopsy (SLNB) is not routinely recommended for thin melanoma. However, it is considered when high‐risk features, clinicopathological, or sociodemographic, are present. It was our objective to evaluate the impact of travel distance on decision‐making for SLNB in thin melanoma. Methods We used the National Cancer DataBase (1998‐2011) to identified patients with thin melanoma (≤1 mm thickness). The primary exposure was distance traveled for care, categorized as short (<12.5 miles), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Despite the utility of SLNB in certain patients with clinically node‐negative melanoma, there has been mixed adherence with national consensus guidelines 6–8 . Overutilization of SLNB may lead to unnecessary postoperative morbidity and increased medical expenditures 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the utility of SLNB in certain patients with clinically node‐negative melanoma, there has been mixed adherence with national consensus guidelines 6–8 . Overutilization of SLNB may lead to unnecessary postoperative morbidity and increased medical expenditures 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Underutilization may lead to the incomplete acquisition of prognostic and staging information 10–12 . Various patient and facility factors have been shown to be associated with SLNB adherence 6–8 . Additionally, facility type has also been implicated in the lack of guideline‐concordance among other cancers, but this has not been explored in melanoma 13–15 …”
Section: Introductionmentioning
confidence: 99%
“…SLNB is performed more frequently in hospitals with more beds, which could be due to high‐volume hospitals serving as academic centers and having more medical staff to complete SLNB. Previous studies have reported higher compliance with SLNB guidelines in academic facilities 22,31,36,37 . The increased performance at academic centers is likely due to greater awareness of guidelines in this setting.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have reported higher compliance with SLNB guidelines in academic facilities. 22 , 31 , 36 , 37 The increased performance at academic centers is likely due to greater awareness of guidelines in this setting.…”
Section: Discussionmentioning
confidence: 99%